The Influence of Islamic Branding and Endorsement on Muslim Consumer Loyalty with Consumer Trust as a Mediating Variable (Case Study of Hijab Zoya) - Nadiah Masyahnda Salsabila; Khusnul Fikriyah (International Conference on Islamic Economic (ICIE), 2026)
This study aims to examine the effect of Islamic branding and endorsement on Muslim consumer loyalty, with consumer trust as a mediating variable, in the case of Zoya hijab products in Surabaya. This study used a quantitative research design and utilized primary data collected through an online questionnaire distributed to 211 respondents selected through purposive sampling. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the help of SmartPLS version 4.0 to assess the validity and reliability of the measurement instruments and to evaluate the structural relationships between variables in the proposed model. The findings show that Islamic branding and endorsement have a positive and significant effect on consumer trust. Furthermore, Islamic branding and endorsement also showed a positive and significant direct effect on consumer loyalty. Consumer trust itself was found to have a positive and significant impact on consumer loyalty. In addition, the results confirmed that consumer trust significantly mediated the relationship between Islamic branding and endorsement and consumer loyalty, indicating that marketing strategies based on Islamic values play an important role in strengthening customer consumer loyalty.